The Model of Ecosystem Risks for Industrial Ecosystems Economic Security - Andrey BYSTROV; Tatyana TOLSTYKH; Nadezhda SHMELEVA; Ayya AGAYEVA (Communications of International Proceedings, 2020)
The article systematizes the problem of economic security in industrial ecosystems. The innovation ecosystem is one of the collaboration schemes for industrial enterprises. New risks of industrial ecosystems economic security are formed in the horizontal model. The article analyzes possible risks and threats in the context of digitalization. The main threats and risks to economic security arising from the actors’ collaboration in the industrial ecosystem are considered. A four-level model of ecosystem risks is presented. A method for assessing the system of economic security of industrial ecosystems is proposed. The practical significance of the research results is the possibility of using certain provisions in the practice of managing industrial enterprises, as well as in the development of program documents and strategies of organizations.
Keywords: Industrial Ecosystems; Economic Security; Actors; Threats; Risks.